Availability, pricing, and affordability of essential medicines for pediatric population in Malawi - Chiumia, Francis Kachidza; Chithope-Mwale, Cynthia; Abikoloni, Felix; Matchaya, Vanessa; Gaviyawo, Tadala; Khuluza, Felix (Frontiers in Pharmacology, 2024)
Objective: Lack of access to essential medicines negatively impacts on the quality of healthcare delivery and increases morbidity and mortality, especially to the vulnerable pediatric population. We assessed the availability, pricing, and affordability of pediatric formulations in Malawi. Methodology: The study was conducted in 76 health facilities (public, faith-based and private pharmacies, and clinics) from the northern and southern regions of Malawi from March to May 2023. We adapted the WHO/HAI method for the assessment of both availability and pricing of medicines. Data on availability were collected from stock card records using a WHO/HAI template and medicine prices were provided by the pharmacy personnel who were managing the facilities. Availability of medicines was calculated as the percentage of facilities which had a stock of the respective medicine at the time of data collection while medicine prices was assessed by calculating the median prices of each medicine. To assess the affordability of the medicines, we calculated the number of days it takes for a person who is receiving the government-set minimum wage to work to pay for a treatment course of common indications. The study was approved by the KUHES ethics committee under the numbers U.12/22/3900 and U.12/22/3903. Results and conclusion: The overall availability of pediatric medicines was 38.1% for public health facilities, 53.7% for private retail pharmacies and drug stores, 49.5% for private clinics and 48.3% for Christian Health Association of Malawi (CHAM) facilities. We found the illegal availability of prescription-only medicines of up to 54% in medicine stores. Medicine median prices were higher in the private clinics followed by retail pharmacies and drugs stores. CHAM had the lowest median prices for medicines of all the sectors. More than 50% of medicines were found to be affordable as less than a day’s wage was required to purchase the treatment. We found poor availability of pediatric formulation among public, CHAM, and private sectors in Malawi. This may affect the quality of care among pediatric patients and therefore contribute to morbidity and mortality in Malawi. The supply of medicines and health commodities needs to consider needs of special populations such as children to achieve universal health coverage.